Edge‐to‐Center Propagation of Photochemical Reaction during Single‐Crystal‐to‐Single‐Crystal Photomechanical Transformation of 2, 5‐Distyrylpyrazine Crystals. Issue 52 (28th November 2022) - Morimoto, Kohei; Kitagawa, Daichi; Sotome, Hikaru; Ito, Syoji; Miyasaka, Hiroshi; Kobatake, Seiya
Abstract: Photomechanical molecular crystals are promising materials for photon‐powered artificial actuators. To interpret the photomechanical responses, the spatiotemporal distribution of photoproducts in crystals could be an important role in addition to molecular structures, molecular packings, illumination conditions, crystal morphology, crystal size, and so on. In this study, we have found that single crystals of 2, 5‐distyrylpyrazine show a smooth single‐crystal‐to‐single‐crystal photomechanical expansion, and the photochemical reaction propagates from the edge to the center of the single crystal. We revealed that the surface effect (special reactivity at the crystal surface) in addition to the cooperative effect (the reaction is facilitated by neighboring molecules) is essential for the edge‐to‐center propagation of the photochemical reaction. Our results would provide a foundation for future studies of the photochemical reaction dynamics in photomechanical molecular crystals. Abstract : The edge‐to‐center propagation of a photochemical reaction during the single‐crystal‐to‐single‐crystal photomechanical transformation was newly found for a 2, 5‐distyrylpyrazine (DSP ) single crystal. This is in contrast to the fact that the photochemical reaction generally proceeds homogeneously in molecular crystals.